2020
DOI: 10.1177/0333102419897621
|View full text |Cite
|
Sign up to set email alerts
|

Urine metabolomics signatures in reversible cerebral vasoconstriction syndrome

Abstract: Background The pathophysiology of reversible cerebral vasoconstriction syndrome is unclear. An unbiased systems-based approach might help to illustrate the metabolite profiling and underlying pathophysiology. Methods Urine samples were collected from reversible cerebral vasoconstriction syndrome patients and matched controls recruited in Taipei Veterans General Hospital. 1H-Nuclear magnetic resonance was used to initially explore the metabolic profile, and liquid chromatography tandem mass spectrometry was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The urine level of 8-iso-PGF 2α was found to correlate with the severity of vasoconstriction, especially during the first week of disease course [ 52 ]. Consistent with the findings from urine samples, a recent study also demonstrated higher 8- iso -PGF 2α in the plasma in patients with RCVS during the acute stage [ 53 ].…”
Section: Pathophysiologysupporting
confidence: 83%
See 1 more Smart Citation
“…The urine level of 8-iso-PGF 2α was found to correlate with the severity of vasoconstriction, especially during the first week of disease course [ 52 ]. Consistent with the findings from urine samples, a recent study also demonstrated higher 8- iso -PGF 2α in the plasma in patients with RCVS during the acute stage [ 53 ].…”
Section: Pathophysiologysupporting
confidence: 83%
“…Similar findings were also observed in another case-control study, which demonstrated not only impaired cerebrovascular reactivity during the acute stage but recovery of the impaired cerebrovascular reactivity in the remission stage in 70% of the cases who received follow-up [ 50 ]. Autonomic dysregulation [ 51 ], oxidative stress [ 52 , 53 ], impaired endothelial repairing capacity [ 54 ], and disruption of the BBB [ 55 , 56 ] might contribute to the altered cerebrovascular reactivity, which are detailed below. Moreover, a recent study identified a panel of microRNAs (miR-130a-3p, miR-130b-3p, let-7a-5p, let-7b-5p and let-7f-5p) that can be used to differentiate patients with RCVS (in acute stage) from controls with nearly 90% accuracy [ 57 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Untargeted metabolomes in urine and serum were performed as described by Hsu et al (Hsu et al, 2019 , 2020 ). Briefly, liquid chromatography tandem mass spectrometry (LC‐MS) analysis involved using an Agilent 1290 UPLC system (ACQUITY UPLC HSS T3 column, 2.1 × 100 mm; 1.8 µm; Waters) coupled with the 6540‐Quadrupole‐Time‐of‐Flight (QTOF) mass system (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, several studies have compared the amino acid neurotransmitter pro les of rats with high-pressure neurological syndrome to those of healthy individuals [2]. Illustrating the neurological metabolic ngerprint of CNS leisure might favor etiological hypotheses [9,10], prevention [11], and therapeutic approaches [12]. However, the integrated neurological metabolic perturbation induced by a great depth of heliox saturation diving has not been investigated.…”
Section: Introductionmentioning
confidence: 99%